ON PSYCHOLOGICAL PRINCIPLES OF COMMUNICATION (Scientific journal of the Fergana State University, 2026)
This article examines the psychological and psycholinguistic principles of communication within the framework of language functioning and speech activity. The study analyzes communication as the primary means of language realization and emphasizes the distinction between speech units and communicative units in a discourse-based approach. Particular attention is paid to the extralinguistic, communicative, cognitive, and linguistic aspects of verbal interaction.The paper discusses the communicative, interactive, and perceptive dimensions of communication, the relationship between the addresser and the addressee, and the influence of internal and external factors on the communication process. Based on theoretical sources and examples from literary texts, the study proposes a classification of communication levels (primitive, manipulative, standardized, conventional, business, playful, and spiritual). The findings indicate that communication effectiveness depends on the psychological state of the participants, their cognitive frameworks, and the cultural context. The article has both theoretical and practical significance for psycholinguistics, communication studies, and speech culture research.